The evolution of electrocardiographic changes in patients with Duchenne muscular dystrophies - Woo Hyun Yoo; Min-Jung Cho; Peter Chun; Kwang Hun Kim; Je Sang Lee; Yong Beom Shin (Korean Pediatric Society, 2017)
PurposeMyocardial dysfunction and dysrhythmias are inevitable consequences of Duchenne muscular dystrophy. We aimed to evaluate specific trends of electrocardiographic changes that reflect the progress of cardiomyopathy in patients with Duchenne muscular dystrophy.MethodsFifty electrocardiograms (ECGs) of 30 patients (ages 1 to 27 years) who had not been prescribed medications for heart failure treatment at the time of examination were retrospectively analyzed and compared with 116 ECGs of age-matched healthy 116 controls. Heart rate, leads with fragmented QRS (fQRS), corrected QT, Tpeak-to-Tend, and Tpeak-to-Tend/QT were analyzed.ResultsThe patients with Duchenne muscular dystrophy failed to show a normal age-related decline in heart rate but showed an increasing trend in the prevalence of fQRS, corrected QT, corrected Tpeak-to-Tend, and Tpeak-to-Tend/QT over time. In the ≤10-year-old patient group, a significant difference was found only in the prevalence of fQRS between the patients and the controls. The prevalence of fQRS, heart rate, Tpeak-to-Tend/QT, and corrected Tpeak-to-Tend demonstrated significant differences between the patients and the controls in the middle age group (11 to 15 years old). All the indexes were statistically significantly different in the ≥16-year-old patient group.ConclusionThe prevalence of lead with fQRS representing regional wall motion abnormalities was higher in the young patients than in the young healthy controls, and this might be one of the first signs of myocardial change in the patients. Markers of depolarization and repolarization abnormalities were gradually prominent in the patients aged >10 years. Further studies are needed to confirm these findings.